2003
DOI: 10.1063/1.1592312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr concentration on the microstructure of Al and the magnetoresistance properties of the magnetic tunnel junction with a Zr-alloyed Al–oxide barrier

Abstract: We studied the composition dependence of the microstructure of Al–Zr alloy films and the tunneling magnetoresistance (TMR) behavior of magnetic tunnel junctions (MTJ) with a Zr-alloyed Al–oxide barrier. A highly stable MTJ with a superior-quality 9.89 at. % Zr alloyed Al–oxide barrier was achieved with 39.5% TMR and a bias voltage of 711 mV at half (Vh) TMR. The microstructure of Al changed systematically from polycrystalline to single phase amorphous to duplex phases composed of an amorphous Al–Zr phase and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…However, Ta-based SVs degrade relatively quickly at elevated temperatures due to interlayer diffusion [3]. In this study, we investigated the effect of a new TiAl [4] and amorphous ZrAl alloy films [5] as under-and capping layer on the thermal stability and interdiffusion behavior of synthetic bottom-SVs at elevated temperatures.…”
mentioning
confidence: 99%
“…However, Ta-based SVs degrade relatively quickly at elevated temperatures due to interlayer diffusion [3]. In this study, we investigated the effect of a new TiAl [4] and amorphous ZrAl alloy films [5] as under-and capping layer on the thermal stability and interdiffusion behavior of synthetic bottom-SVs at elevated temperatures.…”
mentioning
confidence: 99%
“…23 This degradation is often attributed to a lack of uniform interfaces and other defects as a result of the presence of columnar grain boundaries in the polycrystalline precursor metal films prior to oxidation. 24,25 Since a precursor metallic phase in the amorphous state has no grain boundaries, 22 it is reasonable to expect that a continuous thin layer of oxide would form when exposed to an oxidizing atmosphere, causing an improved performance of a MTJ. Indeed, Bae et al reported the initial oxidizing paths of the crystalline precursors were the grain boundaries and then through the grains, leading to the formation of nonuniform interfaces and other defects 26,27 as well as the partial oxidation of the ferromagnetic layer below the tunnel barrier layer before completion of the Al oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Bae et al reported the initial oxidizing paths of the crystalline precursors were the grain boundaries and then through the grains, leading to the formation of nonuniform interfaces and other defects 26,27 as well as the partial oxidation of the ferromagnetic layer below the tunnel barrier layer before completion of the Al oxidation. 28 However, since an amorphous phase was found in Al-Zr alloys via different experimental techniques, 22,[29][30][31][32][33] we choose to use this binary as a model system for both theoretical and experimental investigations in the present study. We will first present a thermodynamic formulation to predict alloy compositions of Al-Zr with tendencies to form amorphous thin films when these films are prepared using rapid quenching techniques such as sputter deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these tunnel barriers have been shown to spin inject with TMRs greater than 50% for Al 2 O 3 and 40% for ZrO 2 or Al 2 O 3 /ZrO 2 mixtures [6][7][8].…”
Section: Introductionmentioning
confidence: 99%